Victimization (Bullying) according to gender approach in school adolescents from Huamanga and Sicuani - Amemiya Hoshi, Isabel (2022)
Introduction. School victimization is a current problem in Peru. Gender approach in analysis allows the adaptation of differentiated intervention strategies. Objective. To determine the risk factors for victimization according to gender approach in school adolescents from cities of Huamanga and Sicuani. Design. Analytical cross-sectional observational. Participants. 1160 students from first to fifth grade from two schools (private and public) in Huamanga and Sicuani. Intervention. Validated survey to identify victims of bullying. Analysis. Desciptive, chi-square, OR (95% CI) and multivariate logistic regression analysis. The SPSS vs. 15 program was used. Main outcome measures. Percentage and risk factors for school victimization. Results. 37.3% of students were found victims. In male gender, “has witnessed a violent act” 1.72 (1.122 - 2.636); in female gender “to live with one of parent” 1.682 (1.072 - 2.641); “live in Huamanga” 1.767 (1.119 - 2.790); and in both genders “having a physical defect” and “parents react with violence when they misbehave” were the most important risk factors. The most reported forms of victimization in both genders were “they gave you nicknames” and “you have been discriminated against”. Direct forms such as “they called you homosexual” and “you have been beaten” prevailed in men, and indirect forms in women. Conclusions. The school victimization is an important problem.  In female gender is related to individual and family characteristics and in male gender to school safety. The direct forms of victimization are related to male gender.